SENGKETA PENERBITAN SERTIPIKAT HAK MILIK DI ATAS TANAH HAK GUNA USAHA - Aldavira Artamevia; Listyowati Sumanto (Fakultas Hukum Universitas Trisakti, 2021)
Land registration is required to guarantee legal certainty and also the certainty of land rights. Land certificate is a strong proof of rights. However, there were cases of multiple certificates, more than one certificate on the same plot of land in Kuantan Singingi Regency. The main problem in this research is what causes overlapping certificates regarding the issuance of certificates of property rights on land that still has the status of PT Wanasari Nusantara's Cultivation Rights. This research is a normative and descriptive legal research by using primary and secondary data, analyzed qualitatively and the conclusions are drawn by using deductive logic methods. The conclusion obtained in this research is that the factors causing the problem of overlapping certificates are because the land registration still does not use a computerized system and does not utilize land registration maps, so that village officials provide wrong information to the National Land Agency.